Content Validation and Utility of a Critical Reflective Inquiry Assessment Tool. Issue 5 (September 2016) - Asselin, Marilyn E.; Fain, James A.
Abstract : A Critical Reflective Inquiry (CRI) Assessment Tool was developed based on the CRI Model to assess reflection in nursing practice. Experienced clinicians evaluated the CRI Assessment for clarity and relevance to the CRI Model and nursing practice utility. Content validity index was calculated for each item in the scale and then averaged across all items. The tool has potential in education and orientation for assessing the depth and focus of reflection and what is learned.